2016
DOI: 10.1371/journal.pone.0156278
|View full text |Cite
|
Sign up to set email alerts
|

How Personality Affects Vulnerability among Israelis and Palestinians following the 2009 Gaza Conflict

Abstract: Can the onset of PTSD symptoms and depression be predicted by personality factors and thought control strategies? A logical explanation for the different mental health outcomes of individuals exposed to trauma would seem to be personality factors and thought control strategies. Trauma exposure is necessary but not sufficient for the development of PTSD. To this end, we assess the role of personality traits and coping styles in PTSD vulnerability among Israeli and Palestinian students amid conflict. We also det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
4
4
0
Order By: Relevance
“…Greater PTSD symptom severity was also associated with greater use of the strategy reappraisal, suggesting it was a maladaptive strategy in the current sample. This is in line with previous research (Canetti et al, 2016; Scarpa et al, 2009; Meiser-Stedman et al, 2014; Valdez and Lilly, 2012; Wilson and Scarpa, 2012). Indeed, Wells and Sembi (2004a) note negative appraisal as a maladaptive strategy in the metacognitive model of PTSD.…”
Section: Discussionsupporting
confidence: 93%
“…Greater PTSD symptom severity was also associated with greater use of the strategy reappraisal, suggesting it was a maladaptive strategy in the current sample. This is in line with previous research (Canetti et al, 2016; Scarpa et al, 2009; Meiser-Stedman et al, 2014; Valdez and Lilly, 2012; Wilson and Scarpa, 2012). Indeed, Wells and Sembi (2004a) note negative appraisal as a maladaptive strategy in the metacognitive model of PTSD.…”
Section: Discussionsupporting
confidence: 93%
“…In this review, punishment was positively associated with and predicted PTSD symptoms (Bennett et al, 2009; Roussis & Wells, 2006). This is consistent with several studies on PTSD and punishment that did not directly focus on the metacognitive model in their research (Canetti et al, 2016; Meiser‐Stedman et al, 2014; Scarpa et al, 2009; Valdez & Lilly, 2012; Wilson & Scarpa, 2012). Further, we found that worry was associated with and predicted greater PTSD symptom severity (Bennett et al, 2009; Roussis & Wells, 2008; Wisco et al, 2013) and metacognitive beliefs (Fergus & Bardeen, 2017).…”
Section: Discussionsupporting
confidence: 89%
“…However, the relationship between worry and PTSD symptoms was not found across all studies (Bennett & Wells, 2010). This was coherent with research using the TCQ that showed worry had a medium effect on PTSD symptoms (Seligowski et al, 2015) and has been associated with and predicted PTSD symptoms (Canetti et al, 2016; Scarpa et al, 2009; Valdez & Lilly, 2012; Wilson & Scarpa, 2012). Meiser‐Stedman et al (2014), however, did not find an association between worry and stress symptoms, or PTSD diagnosis, 6 months after trauma in a sample of adolescents.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations